Hakim Perempuan Dalam Perspektif Islam - Muhammad Aiz (STIT Al-Marhalah Al-Ulya Bekasi, 2017)
This article proves that an existence of women as a judges has continuously became a debatable issue. Furthermore this article agrees with Ibn Jarir al-Tabari that allows men and women to become muftis or judges. This article is in line with Euis Nurlaelawati and Arskal Salim’s argument stating that the high sensitivity of women judges may lead to problem in judges decision making. This research used normative approaches, that may applied and analyzed based on related laws and regulations.